Lexical Semantic Change in Arabic Online News Headlines in the Covid-19 Digital Media Era - Meki Polanda; Nuraman; Ma’mun Johari (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
The Covid-19 pandemic has accelerated the digital transformation of media, intensifying the speed and competitiveness of online news production. In this context, news headlines are increasingly shaped by the need to remain concise, timely, and attention-grabbing, leading to various forms of lexical semantic change through processes of metaphorization, terminologization, and semantic recontextualization. This study aims to identify and analyze lexical semantic change in Arabic online news headlines within the context of digital media. Using a qualitative descriptive approach, the study examines 50 news headlines collected from Al Arabiya, RT Arabic, and Independent Arabia published between 2020 and 2026. The findings indicate that meaning transfer emerged as the most frequent category of lexical semantic change, followed by semantic narrowing through terminologization, while semantic extension occurred less frequently. The selected headlines from Al Arabiya demonstrate a tendency toward technocratic and economically oriented metaphorical framing, RT Arabic shows stronger evaluative and ideologically loaded metaphorical expressions, while Independent Arabia exhibits greater semantic stability through scientific and medical terminology. These findings suggest that the Covid-19 pandemic did not primarily generate entirely new lexical meanings, but rather accelerated pre-existing processes of semantic change within Arabic digital media discourse. The study contributes to Arabic lexical semantics by demonstrating how digital media reshapes lexical meaning through discursive adaptation in contemporary media environments.